In Vitro Motility, Velocity and Capacitation Status of Merino Ram Spermatozoa - Ismaya, Ismaya; Fiztpatrick, L; Summers, P (ANIMAL PRODUCTION, 2012)
The objective of the present study was to determine the effects of Merino rams on the in vitro motility, velocity and capacitation status of ram spermatozoa. Four rams of proven fertility were used in this study. Semen was collected by electro ejaculation. The fresh semen was diluted at four dilutions in Hepes buffered synthetic oviduct fluid. A sample of semen was collected and the motility, velocity and capacitation status of spermatozoa determined and analyzed. The results study showed that motility and velocity of Merino rams spermatozoa were not significantly different. The mean average path velocity (VAP), straight-line velocity (VSL) and curvilinear velocity (VCL) were 91.2 µm/s, 72.2 µm/s and 134 µm/s, respectively. Amplitude of lateral head displacement (ALH), beat cross frequency (BCF) and linearity (LIN) was 5.5 µm, 19.5 Hz, and 54.7%, respectively. During the incubation time, progressively more spermatozoa became capacitated such that at the end of the incubation, 40.9±0.9% was capacitated acrosome-intact and 29±2.5% was capacitated acrosome-reacted. In conclusion, the motility and velocity of Merino spermatozoa were similar among rams. There were differences among rams in the capacitation profile; however there was no significant effect of incubation time and dilution rate on the capacitation status. Keywords: Merino rams, spermatozoa, motility, velocity, capacitation in vitro Animal Production 14(2):104-110